Profile and professional expectations of medical students from 11 Latin American countries: the Red-LIRHUS project - Mayta-Tristan, Percy (2017)
Background Latin America is undergoing a human resource crisis in health care in terms of labor shortage, misdistribution and poor orientation to primary care. Workforce data are needed to inform the planning of long-term strategies to address this problem. This study aimed to evaluate the academic and motivational profile, as well as the professional expectations, of Latin American medical students. Results We conducted an observational, cross-sectional, multi-country study evaluating medical students from 11 Spanish-speaking countries in 2011–2012. Motivations to study medicine, migration intentions, intent to enter postgraduate programs, and perceptions regarding primary care were evaluated via a self-administered questionnaire. Outcomes were measured with pilot-tested questions and previously validated scales. A total of 11,072 valid surveys from 63 medical schools were gathered and analyzed. Conclusions This study describes the profile and expectations of the future workforce being trained in Latin America. The obtained information will be useful for governments and universities in planning strategies to improve their current state of affairs regarding human resources for health care professions.